1-(Ferrocen-1-ylmethyl)-3-methylimidazol-3-ium hexafluoridophosphate - Vincent O. Nyamori; Siphesihle M. Zulu; Bernard Omondi (Acta Crystallographica Section E, 2012)
The crystal structure of the title compound, [Fe(C5H5)(C10H12N2)]PF6, consists of a ferrocene-1-methyl-(3-methylimidazolium) cation and a hexafluoridophosphate anion. The ferrocenyl rings are skewed by 6.7 (4)° from the ideal eclipsed conformation. The interplanar angle between the plane of the substituted cyclopentadienyl ring and that of the imidazole ring is 89.9 (4)°. The crystal packing is stabilized by C—H...F hydrogen bonds.